The effect of melatonin supplementation on muscle recovery - a literature review - Kozłowska, Paulina; Tabian, Alicja; Smęt, Jakub; Chojnacka, Aleksandra Beata; Borawski, Jacek; Burdon-Sajnóg, Julia; Szymona-Kucewicz, Zofia; Bartela, Klaudia Katarzyna; Dusiel, Julia Katarzyna; Wałachowska, Anna (Journal of Education, Health and Sport, 2026)
Introduction and objective: Melatonin is a hormone produced by the pineal gland that influences the synchronization of the circadian cycle. It is responsible for the proper functioning of the human biological clock by regulating the sleep–wake rhythm. The aim of this review is to present the current state of knowledge on the effects of melatonin supplementation on muscle regeneration after injuries, on muscle damage caused by ischemia and reperfusion, and on muscle recovery in older adults. Review methods: All data were collected from publicly available sources. This article’s databases were accessed via PubMed, BioMed Central. A brief description of the state of knowledge: Recent studies show that melatonin, through it’s influence on the human circadian cycle, also affects muscle regeneration. The biological clock coordinates the expression of many genes located in musce tissue that are responsible for muscle development, hypertrophy, metabolism and repair. In addition, the biological clock regulates glucose and lipid metabolism. Therefore, the proper functioning of the biological clock is important for muscle regeneration. Melatonin also exhibits strong antioxidant and anti-inflammatory effects, which protect against the harmful consequences of reperfusion. Moreover, melatonin influences the TGF-β1/Smad2/3 signaling pathway, thereby protecting against muscle fibrosis. Melatonin also increases the expression of the Pax7 protein in muscle cells, supporting the restoration of the satellite cell pool responsible for repairing damaged muscle. Summary: Melatonin supplementation in athletes, older adults, and individuals who have experienced muscle ischemia and reperfusion may support muscle regeneration, thereby accelerating the patient’s recovery and return to everyday life.